PERSEPSI GURU TENTANG KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, TRANSPARANSI, DAN AKUNTABILITAS PENGELOLAAN KEUANGAN SEKOLAH - Johan Pitoyo Jati Karyono (Universitas PGRI Madiun, 2016)
This study aims to: 1) the effect of teachers’ perceptions of transformational leadership principals to the transparency of financial management of the school; 2) knowing effect perseptions teacher of transformational leadership principals to the accountability of financial management school. Population this research is all public school teachers SMA/SMK/MA in Madiun city. Method sampling technique used is sampling produce purpusive sample of 120 responden. Method analysis used in this study is the linear regression analysis simple. Result tests performed showed that perseption head teacher of transformational leadership school dan positive effect on the transparency of financial management of the school; 2) teachers’ perceptions of transformational leadership principals positive effect on financial management accountability school.